Short-Term Ozone Exposure and Daily Mortality in Suburban and Rural Areas of Southern Europe - Maria Angela Doronzo; José Ramón Martinez Fernandez; Diana Gómez-Barroso; María Alonso-Colón; Beatriz Nuñez-Corcuera; Rebeca Ramis (Atmosphere)
Ozone (O3) is a major air pollutant with significant health effects, including increased respiratory and cardiovascular mortality. While previous research has largely focused on urban areas, this study assesses the association between maximum 8 h O3 concentrations and non-accidental mortality, including cardiovascular and respiratory mortality, in suburban and rural areas of Spain. We conducted a nationwide time-series analysis across 122 municipalities between April and September 2017 using Poisson regression models and adjusting for daily maximum temperature and provincial variability. Distributed lag models were applied to estimate the cumulative effects of ozone exposure on mortality, considering lags from 1 to 30 days. For each 10 µg/m3 increase in 8 h maximum O3 concentration, a significant increase in all-cause mortality risk of 2.3% was observed, with a peak at lag 2. Cardiovascular mortality increased by 2.4%, also peaking at lag 2, while respiratory mortality showed the strongest association, with a 4.3% rise at lag 1. A secondary mortality risk increase was observed at lags 24–28, suggesting the potential delayed effects of O3 exposure. These findings showed higher risk than those previously reported for urban populations and highlight the need for targeted public health interventions to mitigate the impact of ozone pollution in non-urban populations.